2014
DOI: 10.1007/s13762-014-0540-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community change through drinking water treatment processes

Abstract: The microbiological quality of drinking water has aroused increasing attention due to potential public health risks. Knowledge of the bacterial ecology in the effluents of drinking water treatment units will be of practical importance. However, the bacterial community in the effluents of drinking water filters remains poorly understood. The changes of the density of viable heterotrophic bacteria and bacterial populations through a pilot-scale drinking water treatment process were investigated using heterotroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Core taxa within the DWTPs comprised primarily of Actinobacteria ( Sporichthyaceae ) , Acidobacteria ( Halophagaceae ), Alphaproteobacteria, Gammaproteobacteria and Betaproteobacteriales ( Rhizobiales, Phreatobacter ). These groups have previously found to be ubiquitous in DWTPs (Pinto et al ., 2012; Lautenschlager et al ., 2013; Zeng et al ., 2013; Liao et al ., 2015a). In this study, these taxa were observed to be dominant in the source waters and showed continued dominance throughout DWTP samples.…”
Section: Discussionmentioning
confidence: 99%
“…Core taxa within the DWTPs comprised primarily of Actinobacteria ( Sporichthyaceae ) , Acidobacteria ( Halophagaceae ), Alphaproteobacteria, Gammaproteobacteria and Betaproteobacteriales ( Rhizobiales, Phreatobacter ). These groups have previously found to be ubiquitous in DWTPs (Pinto et al ., 2012; Lautenschlager et al ., 2013; Zeng et al ., 2013; Liao et al ., 2015a). In this study, these taxa were observed to be dominant in the source waters and showed continued dominance throughout DWTP samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, volatile organic compounds, heavy metal and pathogen contaminations in household pipes were routinely evaluated [ 3 ]. Compared with the numerous reports on bacterial cell concentration and community from drinking water reservoirs [ 4 , 5 ], drinking water treatment processes [ 6 ], and transportation system [ 7 ], the characteristics of water bacterial composition associated with building indoor pipelines remains poorly understood. Recent publications have suggested that drinking water pipeline materials, including metal pipes and polymer pipes [ 8 , 9 ], household stagnation [ 10 ] and temperature [ 3 ] may increase the bacterial regrowth associated with indoor water pipes [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has investigated the bacteria that could reduce some organic matters, and also examined the change in microbial community due to the change in drinking water processes ( Chung et al, 2008 ; Liao et al, 2012 , 2013 , 2014 , 2015b ; Wang et al, 2015 ). However, there is no information on the microbial communities in BAC filters that exposed to phenol, which could contribute to isolating the main indigenous bacteria that has excellent phenol-degrading ability in drinking water biofilters.…”
Section: Discussionmentioning
confidence: 99%